Peningkatan Aktivitas dan Hasil Belajar Siswa pada Materi Sistem Gerak pada Manusia Melalui Penerapan Model Pembelajaran Kooperatif Tipe Two Stay Two Stray (TSTS) pada Siswa Kelas XI MIA 1 SMA Negeri 7 Takalar - Rusnandar, Asrul Mara; Syamsiah, Syamsiah; Hamka L, Hamka L (Universitas Negeri Makassar, 2021)
Abstract. This research is classroom action research conducted over two cycles. The purpose of this study is to improve the activities and learning outcomes of students through the implementation of a Cooperative Learning Model, Two Stay Two Stray. The subject of the study, namely students in grade XI MIA 1 SMA Negeri 7 Takalar. Data collection was carried out in the odd semester of the 2018/2019 school year. The research data collected there are two, namely the activities and learning results of students. The learning activities of the learners were collected during the learning process observed by two observers using observation sheets and the data of the study results obtained through the provision of evaluation tests conducted at the third meeting at the end of each cycle, the final test of the cycle given in the form of multiple choice questions as many as 20 (twenty) items. The data obtained is analyzed in 2 ways, namely qualitative analysis for learner learning activities and quantitative analysis for students' learning results. The results of research on learning activities of students showed an average in cycle I of 64.24% and in cycle II by 70.96%, an increase of 6.72%. The study results also showed an average value increase of 70.16% in cycle I and an average value of 79.84% in cycle II. Through quantitative analysis, it is known that the category of completion of students with the percentage of students completed in cycle I is 64.52% and in cycle II reaches 83.87%. So it can be concluded that the implementation of Cooperative Learning Model; Two Stay Two Stray (TSTS) can improve the activities and learning outcomes of studentsKeywords: cooperative learning, two stay two stray, learning activities, learning outcomes